Hubungan Dukungan Keluarga dengan Kepuasan Hidup pada Dewasa Awal Lajang Secara Sukarela di Maluku - Kaplale, Shinta Nur Hamica; Rohmadani, Zahro Varisna (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The choice to be voluntarily single is a form of individual independence in determining their life path. However, in a collective culture like Indonesia, this chage is often inseparable from social pressure and family expectations. Family support is believed to have an important role in helping individuals interpret their choices positively, which ultimately affects life satisfaction. This study aims to determine the relationship between family support and life satisfaction in voluntarily single people in Maluku. The subjects of the study were 100 early adults selected by purposive sampling. Data collection used a scale of family support and life satisfaction measurement. Statistical data analysis used Spearman Product Moment correlation. The results of this study found that there was a significant relationship between family support and life satisfaction in volunteer single people in Maluku (r = 0.703 and sig=0.000). This means that the higher the family support, the higher the life satisfaction of a person, it is expected to be able to view the status they are living positively as a result of personal choices that are under their control.